China pandemic - Shaw, A. R. (Createspace., 2013)
What the world dreads most has happened -- a mutated avian flu pandemic has ravaged the global population. Whether accidental or intentional, only two percent of the population has survived. In the Pacific Northwest, a dying mother recognizes that her young child is among the immune. What will she do to ensure his survival before her own death? Meanwhile, as natural predators invade urban areas, Graham has buried his last remaining family member and promised to carry out his father's advice to make it to the family cabin. He meets with triumph and tragedy learning new rules along the way. Just when he thinks he's finally got a handle on this new world, he's taken by surprise as he learns he's not alone. A hidden community of Preppers is nearby. Will he find the strength to escape these dangers and go on living? And more importantly, will he have the ability to protect those he's come to trust?
Keywords: Apocalyptic fiction; Avian influenza; Avian influenza -- Fiction